Range size and growth temperature influence Eucalyptus species responses to an experimental heatwave. (10th March 2019) - Aspinwall, Michael J.; Pfautsch, Sebastian; Tjoelker, Mark G.; Vårhammar, Angelica; Possell, Malcolm; Drake, John E.; Reich, Peter B.; Tissue, David T.; Atkin, Owen K.; Rymer, Paul D.; Dennison, Siobhan; Van Sluyter, Steven C.
Abstract: Understanding forest tree responses to climate warming and heatwaves is important for predicting changes in tree species diversity, forest C uptake, and vegetation–climate interactions. Yet, tree species differences in heatwave tolerance and their plasticity to growth temperature remain poorly understood. In this study, populations of four Eucalyptus species, two with large range sizes and two with comparatively small range sizes, were grown under two temperature treatments (cool and warm) before being exposed to an equivalent experimental heatwave. We tested whether the species with large and small range sizes differed in heatwave tolerance, and whether trees grown under warmer temperatures were more tolerant of heatwave conditions than trees grown under cooler temperatures. Visible heatwave damage was more common and severe in the species with small rather than large range sizes. In general, species that showed less tissue damage maintained higher stomatal conductance, lower leaf temperatures, larger increases in isoprene emissions, and less photosynthetic inhibition than species that showed more damage. Species exhibiting more severe visible damage had larger increases in heat shock proteins (HSPs) and respiratory thermotolerance ( T max ). Thus, across species, increases in HSPs and T max were positively correlated, but inversely related to increases in isoprene emissions. Integration of leaf gas‐exchange, isoprene emissions, proteomics, and respiratory thermotolerance measurements provided new insight into mechanisms underlying variability in tree species heatwave tolerance. Importantly, warm‐grown seedlings were, surprisingly, more susceptible to heatwave damage than cool‐grown seedlings, which could be associated with reduced enzyme concentrations in leaves. We conclude that species with restricted range sizes, along with trees growing under climate warming, may be more vulnerable to heatwaves of the future. Abstract : Populations of four Eucalyptus species, two with large range sizes and two with comparatively small range sizes, were grown under two temperature treatments (cool and warm) before being exposed to an experimental heatwave. Visible heatwave damage was more common and severe in the species with small rather than large range sizes. Measurements of leaf gas‐exchange, isoprene emissions, respiratory thermotolerance, and proteomic responses provided new insights into the mechanisms underlying differences in tree species heatwave tolerance. Surprisingly, warm‐grown trees were more susceptible to heatwave damage than cool‐grown trees, which could be associated with reduced enzyme requirements for growth at warm temperatures.